Fluid losses and voluntary fluid intakes in New Zealand age group triathletes during the 1998 ITU World Championship Triathlon - Hellemans, I. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
The aim of this field study was to first estimate sweat induced fluid losses in New Zealand age group triathletes during an Olympic Distance Triathlon race and to secondly provide feedback on fluid losses and fluid needs to individual athletes to assist them in developing appropriate individual fluid plans for use during competition.